Analysis of Node in Wain River Protected Forest - Jordan, Nadia Almira; Endrawati, Budiani Fitria; Ariyaningsih, Ariyaningsih; Susantiningdyah, Healty (LPPM ITK, 2018)
HLSW is a natural tourist attraction that presents the scenery and experience of natural tropical rainforest exploration. The existing space in the HLSW area is not well ordered, especially in the public zone as the zone visited by more diverse visitors. This can be seen from main routes and some attraction nodes that are not in good condition. Node is the concentration of the area, which is the intersection of HLSW main pathway, the tracking post and attraction area as the activity center. A node must show the indigenous character and accommodate the visitor?s activity. It is necessary to analyze the HLSW node to obtain the type of activity and the condition of physical elements. Observation of the node by mosaic technique, which is to combine several single photographs to get the picture in a wide scope and to understand the role of each node. Results of this research are (i) All three types of nodes are exist in natural condition with very minimal facilities, (2) The number of facilities such as signage and other supporting furniture are not good in quality and not many in quantity, (3) The whole elements does not show HLSW character yet. This causes the concentration of the area to be less attractive and does not show its identity.